2021
DOI: 10.1021/acs.nanolett.0c04878
|View full text |Cite
|
Sign up to set email alerts
|

IrCuNi Deeply Concave Nanocubes as Highly Active Oxygen Evolution Reaction Electrocatalyst in Acid Electrolyte

Abstract: Proton exchange membrane water electrolyzer can sustainably and environmentally friendly produce hydrogen. However, it is hindered by the lack of high-performance anode catalysts for oxygen evolution reaction (OER) in acid electrolyte. Herein, IrCuNi deeply concave nanocubes (IrCuNi DCNCs) are successfully synthesized from the selective etching of the facet of cubic nanoparticles, and they significantly boost the OER. The obtained IrCuNi DCNCs show high activity toward OER in the acidic electrolyte, which only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 47 publications
(59 reference statements)
1
51
0
Order By: Relevance
“…Ir possesses a strong binding to O-species, making it effective in dissociating H2O but not in forming O2. 11,14 In this regard, advances in improving the OER activity of Ir have been achieved by alloying Ir with other metals, [17][18][19][20][21][22][23][24][25][26][27] as well as tailoring the geometric morphology of Ir catalysts. [28][29][30][31][32][33][34] The underlying mechanism is to: (i) optimize the intrinsic electronic structure of Ir sites to reach the summit of the activity volcano plot, which is characteristic of catalysts restricted by the scaling relation; and (ii) increase the number of exposed Ir sites in the catalysts.…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…Ir possesses a strong binding to O-species, making it effective in dissociating H2O but not in forming O2. 11,14 In this regard, advances in improving the OER activity of Ir have been achieved by alloying Ir with other metals, [17][18][19][20][21][22][23][24][25][26][27] as well as tailoring the geometric morphology of Ir catalysts. [28][29][30][31][32][33][34] The underlying mechanism is to: (i) optimize the intrinsic electronic structure of Ir sites to reach the summit of the activity volcano plot, which is characteristic of catalysts restricted by the scaling relation; and (ii) increase the number of exposed Ir sites in the catalysts.…”
Section: Main Textmentioning
confidence: 99%
“…S12B). Specifically, the Ir 4f7/2 peak can be deconvoluted into two peaks at 61.3 eV and 62.3 eV, which can be assigned to Ir(0) and Ir(IV), 26,42 respectively. It has been reported that the Ir(IV) oxide layer formed during the reaction is active for OER.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 4 ] However, due to the unsatisfactory thermodynamics and kinetics of both OER and HER, we need to explore a high‐efficiency electrocatalyst to decrease the overpotential and accelerate the reaction speed. [ 5 ] Pt‐based and Ru/Ir‐base oxides precious metals materials and their compounds are considered to be the most effective electrocatalysts for HER and OER. [ 6 ] However, high‐cost and low abundance have severely restricted its wide commercial application.…”
Section: Introductionmentioning
confidence: 99%
“…The water electrolysis was mainly carried out on the surface of an electrode, and thus the surface composition, size, and morphology of the catalysts determined their activity. [8][9][10] Tremendous candidates have been developed to minimize the overpotentials, such as, transition metal alloy, [11] sulfide, [12] oxide, [13] phosphide, [14] and carbon-based nanostructures. [15,16] However, most of them are unstable in harsh acidic environments.…”
mentioning
confidence: 99%